(untitled) (Research, Society and Development, 2021)
Adaptations of education due to the pandemic are affecting half of the world’s students as online and distance learning have become a new routine for some, however, it points out considerable obstacles, as not all students have access. The objective was to describe the impacts of the new Coronavirus pandemic on the teaching-learning access process. Bibliographic study of the type integrative review, the databases Science Direct, Virtual Health Library (VHL), Pub Med and Scientific Electronic Library Online (Scielo) were used, the descriptors used were: “Educational institutions”, “Distance education”” and “Pandemic”. The exclusion criteria were: scientific papers with only available abstracts, duplicate publications and those that did not fit within the proposal offered for the topic and / or were outside the time frame. 1125 articles were found, after the exclusion of duplicate and incomplete findings, it was restricted to 383 works, these were analyzed as to their relationship with the theme and at the end were limited to 9 articles, taking into account those who had the descriptors included in the theme and/or summary. COVID-19 brought with it several disorders, such as the total or partial closure of educational institutions because of the pandemic, which is affecting 890 million students in 114 countries. The impacts of the new Coronavirus pandemic on education have led to many sudden changes in the routine of students, working students, classroom teachers and field practice instructors.